Application of Astrolabe in the Reckoning of Early Player Time - M. Syaoqi Nahwandi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2018)
Astrolabe is a classical instrument in astronomy that is often used to determine the position of celestial bodies without calculating. The notables who played role in the formulation of the astrolabe concept and work system were Hipparchus, Claudius Ptolemy and Theon. Muslim astronomers also had an important role in the development of the astrolabe. The application of astrolabe in reckoning the beginning of prayer time is very easy. But before it can be applied in reckoning prayer time, the astrolabe needs to be equipped with the Sun's altitude lines at the beginning of the prayer time for one year at a location. So the astrolabe can easily be applied to reckon the beginning of prayer times without the need to do calculations. But the Sun's data on the astrolabe are constant as well as the attitude of the Sun at the beginning of prayer time. Those are what reduce the accuracy of the beginning of prayer times reckoning result with the astrolabe.